2021
DOI: 10.1021/acs.langmuir.1c00625
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fluorination of the Surface of Polymeric Materials after Stereolithography 3D Printing

Abstract: With the microfluidics community embracing 3D resin printing as a rapid fabrication method, controlling surface chemistry has emerged as a new challenge. Fluorination of 3D-printed surfaces is highly desirable in many applications due to chemical inertness, low friction coefficients, antifouling properties, and the potential for selective hydrophobic patterning. Despite sporadic reports, silanization methods have not been optimized for covalent bonding with polymeric resins. As a case study, we tested the sila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…While the BV-007A resin yields parts that are moderately hydrophilic, we recently described a method for fluoroalkyl silanization for SLA resins [25]. Here, this method was applied to silanize the BV-007A, and we confirmed that silanization not only increased the three-phase contact angle of a 1x PBS droplet resting on the surface in air, but also when immersed in FC-40 oil (Figure 2c).…”
Section: Selection Of Materials and Print Conditions For Transparency Smoothness Fluorination And Cytocompatibilitysupporting
confidence: 63%
See 2 more Smart Citations
“…While the BV-007A resin yields parts that are moderately hydrophilic, we recently described a method for fluoroalkyl silanization for SLA resins [25]. Here, this method was applied to silanize the BV-007A, and we confirmed that silanization not only increased the three-phase contact angle of a 1x PBS droplet resting on the surface in air, but also when immersed in FC-40 oil (Figure 2c).…”
Section: Selection Of Materials and Print Conditions For Transparency Smoothness Fluorination And Cytocompatibilitysupporting
confidence: 63%
“…Parts printed in BV-007A were silanized using our recently described method [25]. The parts were submerged into a 10% v/v solution of tridecafluoro-1,1,2,2-tetrahydrooctyl trichlorosilane (Gelest Inc., Morrisville PA, USA) in Fluorinert FC-40 (Sigma Aldrich, St. Louis, MO, USA) for 30 min at room temperature.…”
Section: Fluorination Of Resin Surface and Contact Angle Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] For commercial resins, strategies to diminish resin cytotoxicity have started to emerge recently, [27][28][29][30] along with solutions addressing print resolution, [31][32][33][34][35][36] imaging compatibility, 33,[37][38][39] and surface modification and bonding. 40,41 Sifting through the plethora of literature for best practices can be challenging for researchers who are new to this rapidly growing field.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] For commercial resins, resolutions to diminish resin cytotoxicity have started to emerge recently, [28][29][30] along with solutions addressing print resolution, 26,[31][32][33] imaging compatibility, 25,32,34 and other surface modification and bonding. 35,36 Sifting through this literature for best practices can be challenging for researchers who are new to this rapidly growing field, who would especially benefit from more head-to-head comparisons and a systematic analysis of some of the factors that affect biomicrofluidic design in SL printing.…”
Section: Introductionmentioning
confidence: 99%